Factors influencing tax compliance among individual taxpayers - Rabun, Mohd Nazir
Tax compliance is defined as an act performed intentionally and consciously based on obedience, desire, and the ability to comply with tax laws. The degree determines a taxpayer's compliance rate. Regardless of the government's initiatives, including the introduction of penalties, tax compliance remains a significant problem for many countries, as it is difficult to persuade taxpayers to comply with the requirements. Malaysia has just over 1.3 million individual taxpayers from a population exceeding 33.5 million, which translates to only about 4.0 percent of the entire population. This low proportion of individual taxpayers constitutes merely 4.0 percent of the population. Several hypotheses were developed and tested using the descriptive statistics, pearson correlation, and multiple regression techniques in SPSS 27. This study used a quantitative method and convenience sampling to collect 150 completed questionnaires. The results show a significant positive relationship between tax education, tax awareness, tax morale, tax complexity, and tax compliance. Results also show that tax education is the most significant factor influencing tax compliance among individual taxpayers at Pejabat Setiausaha Kerajaan Negeri Perlis (SUK). In conclusion, several recommendations have been put forward to help improve tax compliance among individual taxpayers..